2020
DOI: 10.1590/1982-0275202037e190027
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for antisocial behavior in children: comparison between boys and girls

Abstract: Recognizing the importance of assessing the risk of antisocial behavior, this study aimed to characterize the risk factors for the occurrence of antisocial behavior, seeking to understand if there are differences between boys and girls. Eighty-five cases of children referred by the promotion and protection system due to the display of antisocial behaviors were reviewed. A total of 65 were boys and 20 were girls, aged between six and eleven years. Data collection was performed using the Portuguese version of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Se refiere al comportamiento agresivo, antisocial, encubierto y de oposición desafiante. Comprende actos delictivos como amenazas, agresiones, delitos contra la propiedad y delitos relacionados con sustancias y armas (Coelho et al, 2020;Kerekes et al, 2017;Molero Jurado et al, 2017;Tieskens et al, 2018;Van Cappellen et al, 2023). Los niños y adolescentes con conductas antisociales muestran mayor riesgo de desarrollar resultados negativos como abandono escolar, exclusión social, infracción de la ley, psicopatología y otros problemas relacionados con la salud.…”
Section: Introductionunclassified
“…Se refiere al comportamiento agresivo, antisocial, encubierto y de oposición desafiante. Comprende actos delictivos como amenazas, agresiones, delitos contra la propiedad y delitos relacionados con sustancias y armas (Coelho et al, 2020;Kerekes et al, 2017;Molero Jurado et al, 2017;Tieskens et al, 2018;Van Cappellen et al, 2023). Los niños y adolescentes con conductas antisociales muestran mayor riesgo de desarrollar resultados negativos como abandono escolar, exclusión social, infracción de la ley, psicopatología y otros problemas relacionados con la salud.…”
Section: Introductionunclassified
“…Antisocial behavior is mostly exhibited in childhood. Although this might be considered normal, high levels of antisocial behavior are usually considered a clinical disorder [9]. When young children show hostility towards authority, and older children practice lying, stealing, or even engaging in violent behaviors are some signs of antisocial behaviors [10].…”
Section: Introductionmentioning
confidence: 99%
“…Interactions between parents 3 and their children 4 and their repercussions on human development trajectories constitute a complex phenomenon, since they involve the interplay between multiple variables, such as personal characteristics, sociodemographic conditions of families, and broader sociocultural context in which the family lives. In order to understand the impacts of the context of parenting on the development process of children and adolescents, studies have shown the association between parenting practices and developmental outcomes Borden et al, 2014;Campos, 2019;Sabbag & Bolsoni-Silva, 2015;Trepat et al, 2014), indicating the need for protective government actions, focused on promoting health and preventing possible harm to human development (Coelho et al, 2020).…”
mentioning
confidence: 99%